Using hybrid atomic force microscopy and infrared spectroscopy (AFM‐IR) to identify chemical components of the hair medulla on the nanoscale. (7th August 2021) - Fellows, Alexander P.; Casford, Mike T. L.; Davies, Paul B.
Abstract: Atomic force microscopy integrated with infrared spectroscopy (AFM‐IR) has been used to topographically and chemically examine the medulla of human hair fibres with nanometre scale lateral resolution. The mapping of cross‐sections of the medulla showed two distinct structural components which were subsequently characterised spectroscopically. One of these components was shown to be closely similar to cortical cell species, consistent with the fibrillar structures found in previous electron microscope (EM) investigations. The other component showed large chemical differences from cortical cells and was assigned to globular vacuole species, also confirming EM observations. Further characterisation of the two components was achieved through spectral deconvolution of the protein Amide‐I and ‐II bands. This showed that the vacuoles have a greater proportion of the most thermodynamically stable conformation, namely the antiparallel β‐sheet structures. This chimes with the observed lower cysteine concentration, indicating a lower proportion of restrictive disulphide cross‐link bonding. Furthermore, the large α‐helix presence within the vacuoles points to a loss of matrix‐like material as well as significant intermolecular stabilisation of the protein structures. By analysing the carbonyl stretching region, it was established that the fibrillar, cortical cell‐like components showed considerable stabilisation from H‐bonding interactions, similar to the cortex, involving amino acid side chains whereas, in contrast, the vacuoles were found to only be stabilised significantly by structural lipids.